Situation report on Nepal’s agrifood systems : February 2023 - Minot, Nicholas; Dorosh, Paul A.; Kishore, Avinash; Saroj, Sunil; Krupnik, Timothy J. (CSISA, 2023)
Our assessment of the status of the agri-food system in Nepal during February of 2023 is ‘green’, with data suggesting that prices have remained relatively stable or have followed expected seasonal trends that are unlikely to have caused unusual challenges for smallholder farmers and poor consumers. In December and January of 2022, food prices were generally stable (rice, pulses, and edible oils) or declining (potatoes and tomatoes). The exception was wheat flour, whose price continued its upward trend since mid-2022. This will adversely affect consumers of wheat products, but the availability and stable price of rice as a cereal substitute could to some extent reduce the negative economic impact consumers. The price of lentils and black gram have remained stable, while the prices of potatoes and tomatoes have declined, following an expected seasonal pattern. Edible oil prices have also been stable. As a result of high transport costs, prices for foods generally remain higher in remote areas of the mid-hills, negatively affecting poor consumers that lack significant opportunity for production and marketing.